Exploring Omnichannel Customer Experience And Improvement Opportunities: A Qualitative Study Among Young Consumers Of AZKO - Li Song Wei; Ferdi Antonio (Yayasan Riset dan Pengembangan Intelektual, 2026)
The rapid adoption of omnichannel retail has transformed customer shopping behavior by integrating digital and physical touchpoints into a unified shopping journey. While previous studies have primarily employed quantitative approaches to examine the effects of omnichannel capabilities on customer outcomes, limited attention has been given to understanding customers' lived experiences across multiple touchpoints. This study explores the omnichannel experiences of young consumers at AZKO retail stores in Jakarta using a qualitative case study approach. Data were collected through semi-structured interviews with 26 participants selected through purposive sampling and analyzed using Braun and Clarke's thematic analysis. The findings identified three major themes shaping omnichannel customer experience: Inventory Visibility, Channel Integration, and Human Interaction. These themes were further conceptualized into three proposed constructs: Information Transparency, Cross-Channel Integration, and Service Support, which together form a customer-centered conceptual model of omnichannel experience. The findings indicate that customers evaluate omnichannel retail holistically, emphasizing accurate inventory information, seamless transitions between online and offline channels, and knowledgeable frontline employees as complementary dimensions of a satisfying shopping experience. This study contributes to omnichannel retail literature by developing an empirically grounded conceptual framework that extends existing quantitative research and provides practical guidance for retailers seeking to improve omnichannel integration and customer experience.